2010
DOI: 10.1093/heapol/czq045
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of interventions to prevent cardiovascular disease in Vietnam

Abstract: Contextualization of WHO-CHOICE using local data provides health decision-makers with more sound economic evidence for policy debates on prioritizing health interventions to reduce cardiovascular diseases in Vietnam. When used, cost-effectiveness analysis could increase efficiency in allocating scare resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(130 citation statements)
references
References 46 publications
5
125
0
Order By: Relevance
“…We made an assumption that each patient visited the CHS three times to be screened for hypertension, at 10 minutes per visit. The total cost of screening per person equalled the number of visits multiplied by the cost per primary care visit, taken from a previous study [26,27].…”
Section: Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…We made an assumption that each patient visited the CHS three times to be screened for hypertension, at 10 minutes per visit. The total cost of screening per person equalled the number of visits multiplied by the cost per primary care visit, taken from a previous study [26,27].…”
Section: Costsmentioning
confidence: 99%
“…Drug cost per month was obtained by multiplying number of pills on prescriptions for 338 patients treated at CHS, by prices extracted from an international drug price indicator guide 2013 [28], adding 30% for cost of transportation and distribution [26,29]. Monthly visits to CHS were allocated 20 minutes on average; cost for visits were taken from a citation in a previous study [26,27].…”
Section: Costsmentioning
confidence: 99%
“…There is evidence of a steady increase in temperature of 0.05e0.2 C per decade over the last 5 decades, and the temperature has been predicted to increase by amounts from 1.1 to 1.9 C in low emission scenarios and 2.1e3.6 C in high emission scenarios (Asian Development Bank, 2009). Concurrently, Vietnam has been undergoing an epidemiological transition, in which the overall mortality and morbidity patterns have shifted from communicable to non-communicable diseases (Ha and Chisholm, 2011). A recent study has indicated that one-third of total deaths due to non-communicable diseases were attributed to cardiovascular diseases (CVD), mainly strokes and ischaemic heart diseases (IHD), and the CVDs are ranked first among the causes of mortality in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of cardiovascular disease, there are potential savings for the healthcare budget of between 1.28 and 10.16 million (approximately $60-550) in terms of Vietnamese Dong (VND) per DALY saved by implementing a mass media campaign with messages to reduce salt intake and cholesterol [ 3 ]. From a patient perspective, other research comparing the costs for peritoneal dialysis (PD) and haemodialysis (HD) evidenced that the cost to patients for PD at home was about half than that for the default HD at hospital without impacting on effi cacy [ 4 , 5 ].…”
Section: The Social and Financial Burdenmentioning
confidence: 99%